Blockchain Implementation Simulation for Presidential Voting in Indonesia - Nopendri; Rio Aurachman; Muhammad Rafid Amrullah (Jurnal Rekayasa Sistem & Industri, 2020)
Blockchain has several features that guarantee security and consistency in transaction and data storage.Blockchain has been applied in various fields. The application of blockchain is popular in the financialsector in the form of cryptocurrency. In the political field, the option of implementing blockchain has alsobeen initiated, especially for e-voting process. The idea developed through various researches. Thisresearch tried to propose an initial simulation of blockchain implementation in the presidential election inIndonesia.